A preliminary investigation of the Marine Ichthyofauna in the Tsitsikamma Coastal National Park - C.D Buxton; M.J Smale (Koedoe: African Protected Area Conservation and Science, 1984)
Sixty-five species representing 29 families were re- corded in a survey of the marine ichthyofauna of the Tsitsikamma Coastal National Park. Visual assessments of the composition of the fish communities at three inshore reef types indicated differences in the species composition and size of fishes present. Areas which are closed to fishing protect many species important to the South African linefishery whereas a recent seaward extension of the park boundary in 1983 will also include areas inhabited by species important to the demersal trawl fishery.